2018
DOI: 10.18697/ajfand.83.17000
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with stunting in Dodoma region, Tanzania

Abstract: Child undernutrition is a major public health concern, claiming the lives of numerous children below five years of age in the developing world. The objective of this study was to assess the factors associated with stunting of children of age 6-23 months in Dodoma Municipality and Chamwino District in Dodoma region. Dodoma region located in the central zone of Tanzania was chosen for this study because of its high prevalence (56%) of stunting among children under five years of age. A systematic random sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
(28 reference statements)
3
8
0
4
Order By: Relevance
“…We also found high odds of stunting as child age increases. This agrees with the study conducted in Tanzania [ 41 ] which showed that the risk of stunted increases as children approach their second year of life. Suboptimal breastfeeding (specifically, non-exclusive breastfeeding) and complementary feeding that is limited in quantity, quality and variety could be the factors that increases risk of stunting on children as age increases [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We also found high odds of stunting as child age increases. This agrees with the study conducted in Tanzania [ 41 ] which showed that the risk of stunted increases as children approach their second year of life. Suboptimal breastfeeding (specifically, non-exclusive breastfeeding) and complementary feeding that is limited in quantity, quality and variety could be the factors that increases risk of stunting on children as age increases [ 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study found, stunting in female children decreased by 23% as compared to male child. This agrees with studies conducted in Tanzania, Afghanistan and Ghana [40][41][42] which showed that boys were disadvantaged in term of stunting status than girls. Inadequate amount of food, culture preference and physical activeness might be the leading factors for stunting among male children compared to girls.…”
Section: Discussionsupporting
confidence: 92%
“…Most parents/caregivers in these areas are farmers with primary or no formal education while the few with tertiary education are employed by the state in state institutions. The high occurrence of stunting in children whose parent had tertiary education is unusual when several authors have reported the contrary [ 46 48 ]. This probably highlights the precarious conditions in conflict-hit areas where breakdown in the farm to market channels severely affects even the economically viable.…”
Section: Discussionmentioning
confidence: 99%
“…Most parents/caregivers in these areas are farmers with primary or no formal education while the few with tertiary education are employed by the state in state institution. The high occurrence of stunting in children whose parent had tertiary education is unusual when several authors have reported the contrary [46,47,48]. This probably highlights the precarious conditions in conflict hit areas where breakdown in the farm to market channels severely affects even the economically viable.…”
Section: Discussionmentioning
confidence: 99%